2014
DOI: 10.5152/tjg.2014.4716
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum myeloperoxidase, CPK, CK-MB, and cTnI tests in early diagnosis of myocardial ischemia during ERCP

Abstract: Background/Aims: Some patients may experience retrosternal pain during ERCP, which may be a pioneer of a serious myocardial problem, and early diagnosis is very important for the prognosis and management. In the study, we aimed to investigate the role of serum cardiac biomarkers, such as myeloperoxidase (MPO), creatine phospokinase (CPK), creatine kinase-myocardial band (CK-MB), and cTnI, on early diagnosis of myocardial ischemia during endoscopic retrograde cholangio pancreaticograpy (ERCP) procedures. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…CK-MB and cTnI are two important indicators for the dysfunction of myocardial cells and are widely used in the diagnosis of acute myocardial infarction. 18,19 We found that the expressions of CK-MB and cTnI in H9c2 myocardial cells were significantly elevated by stimulation with LPS, indicating that the dysfunction of myocardial cells was induced by LPS. The LPS-induced dysfunction of myocardial cells was dramatically alleviated by dulaglutide, indicating a promising protective effect of dulaglutide against sepsisinduced myocardial dysfunction.…”
Section: ■ Discussionmentioning
confidence: 79%
“…CK-MB and cTnI are two important indicators for the dysfunction of myocardial cells and are widely used in the diagnosis of acute myocardial infarction. 18,19 We found that the expressions of CK-MB and cTnI in H9c2 myocardial cells were significantly elevated by stimulation with LPS, indicating that the dysfunction of myocardial cells was induced by LPS. The LPS-induced dysfunction of myocardial cells was dramatically alleviated by dulaglutide, indicating a promising protective effect of dulaglutide against sepsisinduced myocardial dysfunction.…”
Section: ■ Discussionmentioning
confidence: 79%
“…CK‐MB and cTnI are classic markers of cardiac injury that are mainly distributed in the myocardium and rapidly released in large amounts in the blood when myocardial injury occurs (Yildiz et al, 2014). The results of the Elisa assay for CK‐MB and cTnI in serum showed that both were significantly lower in the LT group than in the SA group (Figure 3), and cTnI levels were significantly higher in the IBA group as compared with the LT group.…”
Section: Discussionmentioning
confidence: 99%
“…From this, we obtained that sepsis fundamentally affected the systolic and diastolic functions of the myocardium. cTnI and CK-MB are commonly used in clinical evaluation of myocardial status and are specific markers of myocardial injury [ 29 , 30 ]. We noticed that the levels of cTnI and CK-MB were increased in the serum of CLP group, suggesting the cardiac dysfunction of sepsis rat was accompanied by the occurrence of myocardial injury.…”
Section: Discussionmentioning
confidence: 99%